Consumer Behavior: Lifestyle, Socialmedia and Peer Friends on Consumptive Behavior Online Shopping for Fashion Products on The Tiktok Platform: Study on Management Students of Makassar State University - Muhammad Yushar Mustafa; Deddy Ibrahim Rauf; Braem Abraham Killa (International Humanity Advance, Business & Sciences, 2023)
This research discusses the role of lifestyle, social media and peers in consumptive behavior when shopping online for fashion products on the TikTok platform. With the aim of knowing the effect of lifestyle on consumptive behavior, the influence of social media on consumptive behavior, the influence of peers on consumptive behavior. The variables used are Lifestyle (X1), Socialmedia (X2) and Peers (X3) as independent variables and Consumptive Behavior (Y) as the dependent variable. The research approach used is a quantitative approach. The data collection method used is a questionnaire. The population in this study were students of the State Islamic Institute of Bone (IAIN Bone). with a sample of 80 respondents. These data were tested using the Structural Equation Modeling (SEM) technique with the help of the SmartPLS software analysis tool. The results showed that lifestyle (X1) has a significant effect on consumptive behavior (Y) with a sig value of 0.034, which means the value is smaller than α 0.05 or (0.034 <0.05). Social Media (X2) has a significant effect on Consumptive Behavior (Y) with a sig value of 0.000 which means the value is less than α 0.05 or (0.000 <0.05) and Peers (X3) have no effect on Consumptive Behavior (Y) with a sig value of 0.128 which means the value is greater than α 0.05 or (0.000 > 0.05).